Correlation of HbA1c levels in third trimester with maternal and perinatal outcome in patients with gestational diabetes mellitus - R., Pavithra; S., Sreelatha; P., Pooja (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Gestational diabetes mellitus (GDM) is one of the most common metabolic disorders complicating pregnancy. GDM occurs in 2-22% of pregnancies depending on the diagnostic criteria and the epidemiologic characteristics of the population. Elevation of HBA1c have strong correlation with risks of adverse maternal and neonatal outcomes. Aims and objective were to determine the HbA1c levels and to evaluate the maternal and neonatal outcomes in women with HbA1c <5.8% and >5.8% Methods: A retrospective study at ESIC-PGIMSR from June 2021 to December 2021.All mothers diagnosed with GDM using IADPSG criteria were included. HbA1c measured during the 2nd or 3rd trimester. Cut offs of HbA1c in 3rd trimester was taken as 5.8 according to Versantvoort et al. Maternal and neonatal outcome were assessed among two groups i.e., HbA1c <5.8% the control group and HbA1c >5.8% the case group. Demographic, maternal, and infant data were entered and statistical analysis done using SPSS software. Results: Total GDM mothers diagnosed were 152 out of 1454 pregnancies. Incidence is 10.4%. the 38.8% were of 25-30 years age group and 46% were multiparous.48.6% neonates were male and 50.6% were females. Among women with HbA1c >5.8%- Preeclampsia seen in 11 cases (21%), polyhydromnios in 5 cases (11.6%), hypothyroidism in 6 cases (12%) UTI in 1 case (2.3%) and candidiasis in 2 cases (4.6%) while among women with HBA1c <5.8% preeclampsia seen in 20 cases (18.3%), polyhydromnios in 2 cases (1.8%), hypothyroidism in 14 cases (13%) UTI in 2 cases (1.8%) and candidiasis in 4 cases (3.6%). Among women with HbA1c >5.8%-respiratory distress syndrome in 6 babies (13%), hyperbilirubinemia in 9 babies (18.6%), hypoglycemia 2 (4.6%) and hypocalemia in 2 babies (4.6%), 14 babies had normal course (32.5%) while among women with HbA1c 5.8% Among women with HbA1c >5.8%-respiratory distress syndrome in 13 babies (12%), hyperbilirubinemia in 20 babies (18.3%) and hypoglycemia 3 (2.7%). Conclusions: Optimal control of HbA1c along with lifestyle modification and glycemic control helps to reduce maternal and neonatal complications